Komponen Kepemimpinan Transformatif Di Lembaga Pendidikan Islam - Aynun Nurul Ulufah; Achmad Patoni; Binti Maunah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Leadership of transformasional has a positive relationship with subordinate commitment. Transformational leaders are also able to inspire their subordinates to be committed to the vision and mission of the organization's goals, as well as creating strong emotional bonds between leaders and subordinates. This research is based on the context of Islamic educational institutions which require a transformative leader to be able to keep up with changes in line with the times. Through the library research research method, this research explores the components of transformative leadership in Islamic educational institutions. This research provides insight into the contribution of transformative leadership components in leading an Islamic educational institution that can bring change and give rise to innovation.